Recent breakthroughs in blood-based biomarkers of Alzheimer disease: opportunities and challenges in older adults. - Dyer, Adam H; Dolphin, Helena; Roitto, Hanna-Maria; O'Connor, Antoinette; Welsh, Tomas J; Kennelly, Sean P (Age & Ageing, 2026)
Recent advances in Blood-Based Biomarkers (BBMs) are transforming the diagnostic landscape of Alzheimer Disease (AD), with plasma p-tau217 emerging as a highly accurate and scalable diagnostic marker of AD pathology. Across multiple analytical platforms, plasma p-tau217 has demonstrated consistently strong diagnostic performance for the detection of amyloid pathology. The interpretation of BBMs in older adults presents unique challenges due to the high prevalence of multimorbidity, chronic kidney disease, polypharmacy and frailty. Although these factors may influence absolute biomarker concentrations, current evidence suggests the diagnostic performance of p-tau217 remains largely preserved across diverse older populations when interpreted appropriately. Frailty may modify the relationship between AD pathology and clinical expression of mild cognitive impairment/dementia and may influence the absolute concentration of BBMs underscoring the importance of contextualising test results within a comprehensive assessment. Importantly, these factors should not preclude a clinical-biological diagnosis of AD. The clinical value of BBMs such as p-tau217 in older adults lies not in their use in isolation, but in their integration with a gerontologically attuned diagnostic pathway. Current evidence and international guidelines support the use of BBMs only in symptomatic older adults presenting to specialist services and not in asymptomatic individuals. This commentary reviews recent advances in BBM performance, emerging clinical guidelines, real-world evidence and potential diagnostic pitfalls relevant to older adults. We propose that incorporating BBMs within a Comprehensive Geriatric Assessment framework offers a pragmatic approach to achieving timely, accurate and equitable clinical-biological diagnosis whilst preserving the holistic, person centred principles of geriatric medicine.